Pendampingan PIRT sebagai Penguatan UMKM Kuliner di Dusun Eduwisata Kalipucung Kabupaten Semarang - Martien Herna Susanti; Anandha Anandha; Niken Diah Paramita; Ihza Satria Mandala; Ilhan Satria Wirayudha; Anjelina Dwi Widiastuti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This community service program aims to provide assistance in managing Produk Industri Rumah Tangga (PIRT) as an effort to strengthen culinary Usaha Mikro, Kecil, dan Menengah (UMKM) in Kalipucung Educational Tourism Hamlet, Semarang Regency. Kalipucung Hamlet is a fostered village that produces local products made from palm sugar, ginger, and various mushroom products. Most of these products do not yet have distribution permits and their marketing is still limited to the village area and Jambu District. Field analysis revealed two main problems: the lack of understanding among UMKM regarding the function of PIRT as a food safety guarantee and the lack of knowledge regarding PIRT governance. The community service program was implemented in two stages: increasing UMKM knowledge about the importance of PIRT and assistance in the process of managing food safety permits. The methods used included socialization of traditional culinary conservation and understanding of PIRT regulations. Work procedures included team formation, goal formulation, needs identification, solution prioritization, preparation, implementation, mentoring, and evaluation. The results of the activity showed that low interest in traditional culinary, especially among the younger generation, was influenced by unattractive packaging, limited flavor variations, and minimal promotion. Therefore, local culinary conservation needs to be strengthened through PIRT assistance to improve security, legality, and business opportunities, while also supporting the development of tourist villages.